Immediate Implants and Their Use in Clinical Stomatological Practice - K. Kaňovská; P. Prachár (Czech Dental Chamber, 2005)
The authors describe the history and present possibilities to solve deficient dentition by means of immediate implantation. The implants are mostly introduced into alveolus in a certain time lapse after tooth extraction, when the optimal bone structure is optimally restored. Under certain circumstances, if there is a sufficient amount of the bone in the apical area of the extraction alveoli, the endosseous implant can be introduced immediately after the tooth extraction. The communication lists other indications and contraindications of this method. The advantage of immediate implantation lay in the considerably shortened time period between the tooth extraction and placement of definitive substitution, the number of surgical interventions is reduced and the patient accepts better the general therapeutic plan. A certain disadvantage lays in the more complex short-term solution of a temporary substitute due to unsuitable alveolar process and in a potentially higher risk of infection developed for the contamination of the operated on place by microorganisms from the tooth affected by periodontitis. Gradual VNI implants have been recently introduced in the Czech Republic as immediate implants.